Extraction of Oil from Cocoa Shell Waste by Hydrodistillation using Microwave - Nurhamizah, Ibrahim; Nurul Aini, Mohd Azman; Said, Nurdin; Mohd Sabri, Mahmud (AIP Publishing, 2023)
Phytosterols are consumed in many pharmacological products. Cocoa shell is an interesting source as its oil extract has high phytosterol content and potential of valorization. This paper reports application of microwave to control rapid heating assisting hydrodistillation (MAE-HD) of cocoa shell waste (CSW) powder. The objectives were to optimize factors to maximize extraction yield and time. Water to CSW ratio, microwave power and extraction time were varied in One-Factor-At-a-Time (OFAT) manner from 2:1 to 10:1, from 180 to 280 W and from 30 to 150 min, respectively using optimum, predetermined factors. Selected range of the factors was further tested in central composite design. The extract was analyzed by using the Liebermann-Burchard method to measure phytosterol amount. From the response surface of CCD, oil extraction was optimal at 225W for 90 minutes with the water-CSW ratio of 7.94:1 with the yield of 2.46 mass% under significant model of surface functions.